PENGGUNAAN KAPAL PENANGKAP ASING UNTUK KEGIATAN PENANGKAPAN IKAN DI WILAYAH REPUBLIK INDONESIA DIKAITKAN DENGAN ASAS CABOTAGE - Hanif, Ilham; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Regulating the use of foreign fishing vessels in fishing activities in Indonesian waters. This regulation aims to ensure the availability of fish resources, protect traditional fishermen, and optimise the utilisation of national fisheries potential. This regulation sets strict requirements for foreign vessels, such as the obligation to use a base port, employ Indonesian crew members, and pay fisheries levies. In addition, there are restrictions on operating areas, types of fishing gear, and types of fish that can be caught. Strict supervision is carried out through tracking with a vessel monitoring system, vessel inspections, and catch verification. Violations are subject to administrative sanctions up to revocation of operating licences. Thus, KP Regulation 28/2023 seeks to ensure the sustainability of fish resources, protect the interests of local fishermen, and increase state revenue from the capture fisheries sector.Keywords: kelautan, pertahanan, sumber daya alam.